2009
DOI: 10.1051/parasite/2009161029
|View full text |Cite
|
Sign up to set email alerts
|

Tsetse elimination: its interest and feasibility in the historical sleeping sickness focus of Loos islands, Guinea

Abstract: Summary :Guinea is the West African country which is currently the most prevalent for sleeping sickness. The littoral area is the region where most of the recent sleeping sickness cases have been described, especially the mangrove sleeping sickness foci of Dubreka and Boffa where Glossina palpalis gambiensis is the vector. Loos islands constitute a small archipelago 5 km apart from the capital, Conakry. Medical, animal, and entomological surveys were implemented in these islands in Oct-Nov 2006. No pathogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 11 publications
3
17
0
1
Order By: Relevance
“…No significant differences were observed between observed and expected heterozygosities (H E ranged from 5.07 to 19.85 per site, and H O ranged from 3.50 to 20.53 per site). These values are similar to the ones reported for G. f. fuscipes populations around Lake Victoria shores in Uganda [6, 19] and suggest that G. f. fuscipes flies in this region harbor a wealth of genetic diversity and thus have the long term potential to adapt to ecological changes in the area.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…No significant differences were observed between observed and expected heterozygosities (H E ranged from 5.07 to 19.85 per site, and H O ranged from 3.50 to 20.53 per site). These values are similar to the ones reported for G. f. fuscipes populations around Lake Victoria shores in Uganda [6, 19] and suggest that G. f. fuscipes flies in this region harbor a wealth of genetic diversity and thus have the long term potential to adapt to ecological changes in the area.…”
Section: Resultssupporting
confidence: 86%
“…The isolation of northern and southern G. f. fuscipes populations which were thought to occur as a result of fragmentation during extreme drought in East Africa warrants these populations to be treated separately during eradication. Likewise, population study of another tsetse riverine species G. palpalis gambiensis in Senegal also indicated the species was sufficiently isolated and currently eradication is underway [9, 19]. However, population structure of G. p. palpalis in Burkina Faso and G. p. gambiensis in Equatorial Guinea indicated high gene flow compared to other riverine tsetse species [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…From a control perspective, this means that intervention against tsetse in any one site is likely to face reinvasion from the other two. This is different from a similar study conducted on the Loos archipelago, Guinea, which showed that tsetse populations ( G. palpalis gambiensis ) were isolated from the mainland and structured according to the island [15,34], which then allowed a sequential control strategy to be implemented [16,35]. Successful control of tsetse in Abidjan however, would require all three sites to be considered together (Figure 6), either by deploying control measures simultaneously in all three sites, or by a continuous progression of interventions - for example using barriers of impregnated traps and/or targets between sites (Figure 7) following the "rolling carpet" principle [36].…”
Section: Discussionmentioning
confidence: 65%
“…pers. ), à l'image de l'approche utilisée sur les îles de Loos qui a finalement mené au choix d'une stratégie d'élimination (Camara et al, 2006 ;Kagbadouno et al, 2009 ;Solano et al, 2009). Le sex-ratio (mâles/femelles) montre qu'il y a plus de femelles que de mâles capturés.…”
unclassified